PELAKSANAAN KEWENANGAN BADAN PENGAWAS PEMILIHAN UMUM DALAM PELANGGARAN ADMINISTRASI PEMILIHAN UMUM (STUDI TENTANG PENANGANAN PELANGGARAN ADMINISTRASI PEMILU DI BAWASLU PROVINSI SULAWESI TENGGARA) - Kurnaiwati, Wa Ode Intan; Yusuf, Niken Yulian; Supriadi, Supriadi; Yusuf, M.; Ismail, La Ode; Ramadham Soniwaru, Muhammad Syahrir; Tamar Yakub, L.M Yakda (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2024)
The authority of Bawaslu as a state institution that has the authority, namely the authority to oversee the stages of organizing general elections and to adjudicate disputes over the general election process must be in accordance with the state constitution in its implementation so as not to cause the actions or decisions issued by Bawaslu to be defective in authority. The research method used is empirical normative legal research with a statutory approach. The results showed that: 1) The implementation of the authority to carry out election supervision has been in accordance with the state constitution and the rules of Election law in this case Law No. 7 of 2017 concerning General Elections and technical regulations for the implementation of Bawaslu's authority by carrying out the functions of preventing violations by increasing community / public participation. 2) The implementation of the authority to adjudicate election process disputes consisting of election administrative violations and election process disputes, Bawaslu institutionally has carried out this function optimally.